Effectivity of Iron Supplementation With and Without Vitamin C for Increasing Hemoglobin Levels Among Women Aged 16-21 Years Old - Jessica Lauryn; Freggy S Joprang; Angela Kurniadi; Leonardo Leonardo; Fransiskus Xaverius Rinaldi; Erlina Erlina; Gregiorio Gavriel Singgih (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Anemia can be caused by a decrease in hemoglobin (Hb) levels, chronic disease, severe bleeding, nutritional deficiency, and infectious diseases. Iron deficiency is the most common cause of anemia (50%). Vitamin C has an important role in increasing absorption of iron in the body which can indirectly affect the increase in Hb formation. This study was conducted to determine whether iron and vitamin C supplementation affect the changes of Hb levels in women. This study was done by quasi experimental with single blind pretest posttest control group and with a stratified random sampling technique. Respondents were female students in Faculty of Medicine UNIKA Atma Jaya. The total number of sample was 58 which was categorized into two groups. The first group was given iron and vitamin C supplementation. The second was only given iron supplementation. There were 16 respondents (27,6%) aged 16-18 and 42 respondents (72,4%) aged 19-21. The average change in Hb level before and after intervention in group 1 was 1,934 g/dL, and P = 0,000 (P <0,05), the average change in Hb level before and after intervention in group 2 was 1,086 g/dL, and P = 0,000 (P <0,05). The difference of change in Hb levels in groups 1 and 2 had an average of 0,848 g/dL, and P = 0,005 (P <0,05). For conclusion, Iron and vitamin C supplementation has a greater impact on the changes of Hb levels compared to iron supplementation only.